Obstetric challenges during COVID-19 pandemic: A narrative review - Ehab Helmy Abdel Malek Fahmy; Yeap, Boon Tat; Dg Marshitah Pg Baharuddin; Abdel Mohsen Mohamed Ahmed Abdel Hafez; Win Win Than; May, Zaw Soe; Mohd Firdaus Mohd Hayati; Yeung, Sing Chin (Elsevier Ltd, 2021)
The severe acute respiratory coronavirus 2 (COVID-19) pandemic impacts the health of women at reproductive age in different ways, starting from pregnancy planning to post-delivery. This narrative review summarises the challenges to obstetric practice posed by the severe acute respiratory coronavirus 2 (COVID-19) pandemic. In this paper, we highlight the impacts of COVID-19 to obstetric practice globally and the efforts taken to address these challenges. Further study is critical to investigate the effects of COVID-19 on pregnancy, the outcome of COVID-19 positive pregnant women, and the safety of vaccination during pregnancy and breastfeeding.